Cultural Diffusion from China to Pakistan via the China-Pakistan Economic Corridor: A Study of Mandarin Learning in Gilgit Baltistan of Pakistan - Ali , Tajwar; Sultan , Haseena; Alam, Aftab (Pakistan Journal of Humanities and Social Sciences, 2023)
The China Pakistan Economic Corridor (CPEC) is an enormous South Asian development initiative, with the Gilgit Baltistan region of Pakistan functioning as its entrance point. This enormous endeavor has caused cultural diffusion from China to Pakistan. CPEC is disseminating the non-material culture of China, which is the language spoken in Pakistan's northern regions, as evidenced by the growing prevalence of Mandarin in Gilgit Baltistan since the 2013 launch of CPEC. This study examined the effect of CPEC on the acquisition of Mandarin in Gilgit Baltistan. After distributing 150 questionnaires to Chinese-studying students in Gilgit Baltistan, we received 126 responses via online Google form and print form. The current data set yielded positive results that supported the preponderance of hypotheses. Using a method involving a confined group discussion, the influence of the Chinese language on local languages was observed, and the results were presented. The findings of this study will aid cultural ambassadors, government officials, and other relevant parties in gaining a better understanding of Pakistanis' attitudes toward acquiring Mandarin and Chinese culture.